The Influence of Perceived Risk and Travel Constraints to Travel Intention of Women Traveler in Bandung City - Iqlima Ramadhani (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
This study aims to investigate the influence of perceived risk and travel constraints to travel intention of women travelers in Bandung city. A quantitative study was conducted in this research and data were collected from 350 women travelers in Bandung City using purpose sampling. The theories used in this research about perceived risk, theories about travel constraints, and theories about travel intentions. The results of this study revealed that the perceived risk and travel constraints significantly affected the travel intention of women travelers in Bandung by 81.5% while the remaining 18.5% was influenced by other variables not observed in this study. In this case, special attention is needed related to the existing security conditions in the city of Bandung relating to criminal acts that occur. In addition, optimizing women travelers as one of the largest segmentation in the tourism industry, in this case tourism service businesses, especially travel agents can take advantages of this momentum by creating and providing a special tour package for women travelers.